The Effect Of Additional Income On Employee Performance At The Regional Secretariat Office Dairi Regency - Herbet Darwin Sianturi; Muhammad Isa Indrawan (Yayasan Multidimensi Kreatif, 2024)
This type of research is a causal associative quantitative research with the aim of analyzing the pattern of relationships between two variables and determining the influence of Additional Income on Employee Performance. This research was carried out at the Dairi Regency Regional Secretariat Office, with a population of 160 employees. The sampling technique used is a simple random sampling technique, which is a random sample selection from the existing population. The data used came from the results of a questionnaire distributed to respondents consisting of all employees in various divisions. The results of the study show that Additional Income has a positive and significant effect on Employee Performance. This is evidenced by a t-count value of 15.888 which is greater than the t-table 1.65443, as well as a significance value of 0.000 which is smaller than 0.05. A regression coefficient of 1.077 indicates that every 1 point increase in Additional Income will lead to an increase in Employee Performance by 1.077 points, assuming the other variables remain constant. In addition, the results of the determination coefficient test (Adjusted R Square) showed a value of 0.577 or 57.70%, which shows that Additional Income has a very high influence on Employee Performance, with the remaining 42.30% influenced by other factors that have not been studied in this study. Overall, the results of this study identify that the increase in Additional Income can contribute to the improvement of Employee Performance at the Dairi Regency Regional Secretariat Office.